VD_FINDINFO Jug / 2011 / 89 vom 23. März 2011 - VD Tribunal cantonal (2011)
RETRAIT DE L'AUTORITÉ PARENTALE, INTERNATIONAL, FRANCE | 311 al. 1 ch. 1 CC, 311 al. 1 ch. 2 CC, 311 CC, 85 al. 1 LDIP, 174 al. 2 CDPJ